A framework linking ecosystem services and human well‐being: Saltmarsh as a case study. Issue 4 (1st October 2019) - Rendón, Olivia R.; Garbutt, Angus; Skov, Martin; Möller, Iris; Alexander, Meghan; Ballinger, Rhoda; Wyles, Kayleigh; Smith, Greg; McKinley, Emma; Griffin, John; Thomas, Merryn; Davidson, Kate; et al.
Abstract: The ecosystem services approach is based on the interdependencies between nature and human well‐being. However, while the ecosystem services aspect of this approach is well‐developed, the human well‐being aspect remains unstructured and vaguely defined. An integrated conceptual framework was developed by adapting and linking the UK National Ecosystem Assessment‐Follow On framework with human well‐being domains. As well as benefits, the notion of disbenefits was incorporated to recognise the potentially detrimental effects from interacting with nature. Benefits and disbenefits occur at the social–ecological interface and are classified by the seven domains of human well‐being they affect. The framework is applied to saltmarsh habitat as a case study, highlighting knowledge gaps and the potential applicability and usefulness of the framework. In saltmarsh,  benefits mainly accrue at larger scales with a greater impact affecting local to global individuals, while disbenefits tend to occur at a smaller scale and impact in‐situ individuals. The framework provides in‐depth insight into links, trade‐offs and dichotomies between benefits and disbenefits and human well‐being, and improves accessibility to the complex research area of human well‐being. This research can be a useful tool to guide environmental and health policy and management, as well as stakeholder engagement. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.